History Politics of Belarus: Peripeteias of Evolution - A. M. Ponamareva (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Amidst the sharp escalation of great-power rivalry on the world stage, almost all spheres of public life are facing increasing politicization and even securitization. Historical studies are no exception, as they are becoming an essential element of governments’ efforts to strengthen the ideological cohesion of their societies by revisiting history and constructing new historical narratives. Given the significance of the strategic partnership with the Republic of Belarus for the Russian Federation, the study of history politics of the former is of particular interest and relevance. This paper attempts to identify the logic of the Belarus official historical narratives’ transformation since independence up to and including 2024. The research provides a discourse analysis of a wide range of primary sources, i.e. legal acts, media materials, political speeches, reports from official institutions in charge of the implementation of Belarus’s politics of memory. Its evolution falls into several stages, each being a result of a complex intermix of domestic, foreign policy and economic factors, as well as attempts by the republic’s leadership to maneuver between its eastern and western neighbors. The author concludes that the corpus of scholarly texts, documents and ‘places of memory’ created over the years of the republic’s independence contains various ‘entry points’ allowing the government to change its historical policy in almost any way to its liking. This situation persists despite the noticeable decrease of the Republic of Belarus leadership interest in accentuating the European component of national memory after the events of August 2020, and, on the contrary, a pronounced rapprochement with the Russian historical narrative (primarily with regard to the World War II). The author claims that in these conditions, an uncritical perception of common historical memory as an unshakable cornerstone underlying the unity of the Belarusian and Russian peoples may prevent Russia from adequately predicting possible changes in the geostrategic aspirations of its partner.